Analisis Perlindungan Hukum Terhadap Konsumen yang Dirugikan dalam Transaksi Jual Beli pada Situs Belanja Daring - Ela; Solaiman, Eman (Alauddin Law Development Journal (ALDEV), 2023)
This study analyzes the legal protection of consumers who are at a loss in buying and selling transactions on online shopping sites. This research is expected to provide benefits both scientifically in the study of legal science, as well as practically and academically, which can be used as input for writers for those who have a desire to analyze the process of buying and selling online and the responsibility of business actors to consumers. who are disadvantaged in buying and selling transactions on online shopping sites. The research method used in this study is a normative juridical research method, namely research refers to legal norms that exist in legislation, literature, opinions experts, papers. The author analyzes how the responsibility of business actors to consumers who are at a loss in buying and selling transactions on online shopping sites. The law used in this research is Article 7 letter g of the Consumer Protection Act, so business actors are obliged to provide compensation, compensation and/or replacement if the goods and/or services received or used are not in accordance with the agreement.